2017
DOI: 10.1071/en16190
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of fluorotelomer alcohols at two Alpine summits: sources, transport and temporal trends

Abstract: Environmental context. The transport and fate of organic pollutants such as fluorotelomer alcohols (FTOHs) in the atmosphere affect their risks to the environment and human health. On the basis of hourly trajectory predictions, we found that, from 2007 to 2010, individual levels of 6:2, 8:2 and 10:2 FTOH were from nondetectable to 72.4 pg m À3 at two Alpine summits. Air mass origin was an important factor determining the Alpine atmospheric FTOH levels.Abstract. The transport and fate of fluorotelomer alcohols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…This trend is consistent with our knowledge of commercial product formulations and atmospheric measurements (Dinglasan-Panlilio and Mabury, 2006;Heydebreck et al, 2016;Young and Mabury, 2010). Despite producers moving from 8:2 to shorter-chain formulations, recent FTOH 30 atmospheric measurements have found that the 8:2 FTOH remains the dominant compound in the High European Alps (Xu et al, 2017). Therefore, it is likely that PFCAs from PFPeA to PFUnDA on the Devon Ice Cap are derived from common emission sources due to prominent quantities of residual volatile precursors in fluoropolymer products.…”
Section: Pfca Homologues and Volatile Precursorssupporting
confidence: 71%
“…This trend is consistent with our knowledge of commercial product formulations and atmospheric measurements (Dinglasan-Panlilio and Mabury, 2006;Heydebreck et al, 2016;Young and Mabury, 2010). Despite producers moving from 8:2 to shorter-chain formulations, recent FTOH 30 atmospheric measurements have found that the 8:2 FTOH remains the dominant compound in the High European Alps (Xu et al, 2017). Therefore, it is likely that PFCAs from PFPeA to PFUnDA on the Devon Ice Cap are derived from common emission sources due to prominent quantities of residual volatile precursors in fluoropolymer products.…”
Section: Pfca Homologues and Volatile Precursorssupporting
confidence: 71%